PMC, a potent hydrophilic α-tocopherol derivative, inhibits NF-κB activation via PP2A but not IκBα-dependent signals in vascular smooth muscle cells - Hsieh, Cheng-Ying (Blackwell Publishing Ltd, 2014)
The hydrophilic α-tocopherol derivative, 2,2,5,7,8-pentamethyl-6-hydroxychromane (PMC), is a promising alternative to vitamin E in clinical applications. Critical vascular inflammation leads to vascular dysfunction and vascular diseases, including atherosclerosis, hypertension and abdominal aortic aneurysms. In this study, we investigated the mechanisms of the inhibitory effects of PMC in vascular smooth muscle cells (VSMCs) exposed to pro-inflammatory stimuli, lipopolysaccharide (LPS) combined with interferon (IFN)-γ. Treatment of LPS/IFN-γ-stimulated VSMCs with PMC suppressed the expression of inducible nitric oxide synthase (iNOS) and matrix metalloproteinase-9 in a concentration-dependent manner. A reduction in LPS/IFN-γ-induced nuclear factor (NF)-κB activation was also observed in PMC-treated VSMCs. The translocation and phosphorylation of p65, protein phosphatase 2A (PP2A) inactivation and the formation of reactive oxygen species (ROS) were significantly inhibited by PMC in LPS/IFN-γ-activated VSMCs. However, neither IκBα degradation nor IκB kinase (IKK) or ribosomal s6 kinase-1 phosphorylation was affected by PMC under these conditions. Both treatments with okadaic acid, a PP2A-selective inhibitor, and transfection with PP2A siRNA markedly reversed the PMC-mediated inhibition of iNOS expression, NF-κB-promoter activity and p65 phosphorylation. Immunoprecipitation analysis of the cellular extracts of LPS/IFN-γ-stimulated VSMCs revealed that p65 colocalizes with PP2A. In addition, p65 phosphorylation and PP2A inactivation were induced in VSMCs by treatment with H(2)O(2), but neither IκBα degradation nor IKK phosphorylation was observed. These results collectively indicate that the PMC-mediated inhibition of NF-κB activity in LPS/IFN-γ-stimulated VSMCs occurs through the ROS-PP2A-p65 signalling cascade, an IKK-IκBα-independent mechanism. Therapeutic interventions using PMC may therefore be beneficial for the treatment of vascular inflammatory diseases.